Urban Form Types and Some Related Social Problems of Multistorey - Faisal Hameed Hameed; Mohammed Areare Areare (Iraqi Journal of Architecture and Planning, 2018)
The urban expansion of the Gulf cities included many multi-storey housingprojects of urban form types similar to those built in Britain during the postSecond Wold War period of reconstruction. According to the literature, thesetypes of urban form are associated with a number of social problems in relationto the health of some residents, anti-social behaviour of some youngsters, andsome types of crime. The aim of this research is to identify the types of urbanform in the context of the British built environment and to conduct a pilot studyto investigate the presence of social problems in Gulf housing projects whichencompass urban forms similar to those built in Britain during the post SecondWold War period. The conclusion is that some social problems can be traced insome of the projects inspected in the study. The study suggest further in depthresearch to determine the extent of such social problems and suggest designsome guidance for new projects in order to avoid such problems.